Green finance development and environmental sustainability: A panel data analysis - Khan, Soha; Akbar, Ahsan; Nasim, Ismat; Hedvičáková, Martina; Bashir, Furrukh (Frontiers in Environmental Science, 2022)
The study is considering five regions South Asia, Southeast Asia, China, middle east countries, European Countries for the period of 15 years. This study will a significant addition in literature by providing the evidence of green finance impact on environment sustainability. The green finance development is represented by inclusion of GDP, investment in renewable energy sources, R&D for eco-friendly projects and public private partnership investment in renewable energy projects. Green financing development in the chosen panel exhibits a distinct geographical cluster effect, with significant regional variances. The most important influencing elements are regional GDP, regional innovation level, and air quality, whereas the degree of financial development and industrial structure optimization are insignificant. The degree of financial development and industrial structure optimization are related to the amount of green finance development mostly via spillover effects. The degree of financial development has a positive spillover impact, but industrial structure optimization has a negative spillover effect. The study revealed that increase in production of energy from renewable sources, increase in research and development and the evolution of public-private-partnership investment in renewable energy causes decrease in CO2 emission. It is evidenced that green finance in renewable energy sources is necessary to achieve environmental sustainability. There is strong need to increase the green finance in renewable sources to target the vindication of global CO2 emissions. There should be cross-border trade of renewable energy in the regions/countries to mitigate CO2 emissions in the whole world. The study ranked regions on the basis of environmental sustainability that may help out the researchers and decision makers to entice foreign direct and private investment in such regions. The implications of findings of the study conclude that environmental sustainability benefits greatly from green financing and investing in renewable energy sources through public-private partnerships is one of the greatest ways to ensure environmental sustainability.